The True Identity of Putative Tooth Alveoli in a Cenozoic Crown Bird, the Gastornithid Omorhamphus - Louchart, Antoine; Bhullar, Bhart-Anjan; Riamon, Ségolène; Field, Daniel J. (Frontiers in Earth Science, 2021)
All extant birds are toothless, and recent molecular evidence suggests that edentulism in extant birds is the product of a single evolutionary transition to toothlessness on the line to crown birds in the Cretaceous. However, a fossil crown bird premaxilla from the Palaeogene of North America (assigned to the gastornithid Omorhamphus storchii) has been interpreted as bearing alveoli for teeth, an observation that would cast doubt on a single loss of teeth preceding the extant avian radiation. However, the identity of these putative alveoli has never been reinvestigated in detail. Here, we re-examine this problematic juvenile specimen, using non-invasive x-ray microtomography, enabling the assessment of the true identity of the large, alveolus-like pits on the ventral side of this premaxilla. Although superficially alveolus-like, we illustrate that these pits represent openings of large neuro-vascular canals communicating with both the medullary cavity as well as other canals opening along the dorsal and lateral surfaces of the upper jaw, and that none of these openings appear to represent tooth alveoli. Further, we demonstrate that claims of an adult gastornithid specimen (Gastornis parisiensis) exhibiting tooth alveoli are similarly unfounded. By rejecting the hypothesis of dentition in these gastornithids, we eliminate any lingering uncertainty regarding the persistence of teeth within the avian crown group. We illustrate the presence of similar large vascular openings along the ventral surface of the beak of juvenile Gastornis russelli/parisiensis, and smaller versions in the juvenile premaxillae of Sylviornis neocaledoniae. We suggest that the large vascular canals in gastornithid specimens such as O. storchii are a feature associated with rapid growth of the juvenile beak, allowing the attainment of a large and dorsoventrally deep beak early in ontogeny. This may have enabled young gastornithids to become autonomous early, consistent with a presumably precocial developmental strategy.